La tradición intelectual de origen continental europeo en la formación de los juristas - Martínez López, Jose Luis (Revista de Derecho, 2019)
This essay is based on the dissertation delivered by the author upon his appointing as Honorary Professor of the University of Piura, in which he make a comparative analysis between the law’s characteristic knowledge and teaching in the European continental and in the Anglo-American traditions. Since the origin of the European universities, lawyer’s training was founded in the possibility of a rational, etiological, critical and systematic knowledge of the human being and his social requirements, and therefore of the law as well, getting to generate, along the centuries, and, with a particular development since the nineteenth century, in the European continental area, a solid law science, with mature achievements, largely spread all over the world, although it has also had to overcome no few failures, some among them with disastrous social results, and indeed its progress has not a completely secure protection from the backward steps. This dissertation sustains that, even within theirs limits, the law’s characteristic knowledge and teaching in the European continental area consolidate tradition present noticeable advantages over the different reality of the law experience and learning in Anglo-American world, based in a empirical pragmatism, imbued with a reluctance to an properly scientific approach rooted in the cultural break represented, in the fourteenth century, by Ockham nominalism.